Utilizing the Tact Maxim as a Host When Interviewing Guests on the Kick Andy Talk show 2019 - I Gusti Ayu Agung Sintha Satwika,; I Gusti Ayu Agung Dian Susanthi, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The role of the host is directly tied to communication. The host needs to be able to get the information they need while still being polite. The purpose of this study is to determine how the tact maxim is applied and formulated as a politeness strategy. Note-taking and non-participant observation techniques were used to gather the data for this study, which can be found on the official Kick Andy YouTube channel and website. This study made application of Leech's (2014) politeness theory, which talks about tact maxims. According to the study's findings, the host of the 2019 Kick Andy talk show applied the tact maxim, one of the neg-politeness maxims, to lessen the amount of pressure placed on the guest. Declarative and interrogative structured utterances, interrogative utterance, subtle imperative, and conditional relationship clause are all used to realize the tact maxim. It can be concluded that the host can obtain sufficient information while remaining polite by implementing the tact maxim, which is a form of politeness. As a result, the interview goes well, and the host's questions don't burden the guest.